2012
DOI: 10.1093/carcin/bgs311
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of TIMP3 hypermethylation in post-treatment salivary rinse from head and neck squamous cell carcinoma patients

Abstract: Hypermethylation in the promoter regions of genes is associated with suppression of gene expression and has been considered a potential molecular marker for several tumor types, including head and neck squamous cell carcinomas (HNSCC). Moreover, hypermethylation can be detected in body fluids such as saliva and can be useful for the diagnosis and prognosis of patients suffering from cancer. To evaluate the hypermethylation profile as a tool for early detection of tumor recurrences, this study determines the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 30 publications
5
42
0
Order By: Relevance
“…Since variations in the patterns of promoter hypermethylation in individual tumours may occur depending on alterations on specific molecular pathways, the use of multiple genes may provide greater applicability and coverage for different tumours when compared with a single gene for general detection, corroborating to results obtained by Carvalho et al [23] and Rettori et al [14] in different cohorts. From the initial screening of eight genes, four genes were selected as part of a panel to distinguish OSCC patients and healthy controls.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Since variations in the patterns of promoter hypermethylation in individual tumours may occur depending on alterations on specific molecular pathways, the use of multiple genes may provide greater applicability and coverage for different tumours when compared with a single gene for general detection, corroborating to results obtained by Carvalho et al [23] and Rettori et al [14] in different cohorts. From the initial screening of eight genes, four genes were selected as part of a panel to distinguish OSCC patients and healthy controls.…”
Section: Discussionsupporting
confidence: 77%
“…Carvalho et al [16] were able to confirm an elevated rate of promoter hypermethylation detected in HNSCC patient salivary rinses by using a panel of gene promoters previously described as methylated in HNSCC but not in control subjects, by the same group [23]. Rettori et al [14] in the analysis of salivary rinse samples taken at diagnosis of HNSCC patients, five genes (CCNA1, DAPK, DCC, MGMT and TIMP3) showed high specificity and sensitivity [24]. Thus, the detection of DNA methylation in body fluids opens the potential to develop biomarkers that can be useful for clinical use.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The broad collection of exfoliated epithelial cells across the oral cavity may be advantageous in the assessment of epigenetic alterations in the tumor cells and/or surrounding epithelium. While a number of studies have reported on the diagnostic potential of DNA methylation markers in oral rinse [9-19], few have evaluated the prognostic value [18, 20-22], and those that did were focused solely on promoter methylation of a limited subset of candidate tumor suppressor genes. Such a candidate approach has clear limitations, particularly given our incomplete understanding of genes involved in the biology of head and neck cancer and the crucial involvement of CpG methylation outside of the context of promoter regions in transcriptional regulation and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%